Doing Ethnography in Criminology Discovery through Fieldwork (Springer International Publishing, 2018)
This innovative book examines the use of ethnography and fieldwork in Criminology and Criminal Justice Research. Using a combination of case studies, as well as "behind the scenes" contributions, it provides an comprehensive look at both the insights gained from ethnographic research, as well as the choices researchers make in conducting that work. The research is divided into three main sections, covering ethnographies of subcultures, ethnographies of place, and ethnographies of policing. It includes a diverse group of international contributors to provide perspectives on researchers' selection of questions to study, and their decisions about using ethnography to study those questions. This work will be of interest to researchers in criminology and criminal justice, particularly with a qualitative perspective, as well as related fields such as sociology, anthropology, and demography. It will also be of interest to students studying research methods and design.